Improvement of Electrical Power System Dynamic Stability Using Fuzzy Logic - Setiawan, Paulus (Sekolah Tinggi Teknologi Adisutjipto, 2018)
This research has an aim to know the effectiveness of fuzzy logic which takes over the controlling of Proportional Integral Derivative (PID) in repairing the dynamic stability of electrical power system. This research begins with making the mathematic model of electrical power system into a circumstances variable equation and the plant system diagram block model. The structure of fuzzy logic controller system is designed by using 2-input which has three, five, and seven membership functions. The formed system work test is conducted by giving a disruption of increase and decrease electric power, to perceive the result of dynamic order on system variable to rotor speed deviation, angle rotor, voltage terminal, and power electric. Fuzzy logic can increase PIDPSS performance in repairing the electrical power system dynamic stability. The overshoot value decrease to 73.881% - 89.069% and settling time is 57.81% - 67.01% to the rotor speed deviation.